Accounting Treatment for Heritage Assets: A Case Study on Management of Pari Temple - Heri Widodo; Nur Ravita Hanun; Retno Wulandari (Journal of Accounting and Investment, 2020)
Research Aims: This research is conducted to find out how the accounting treatment of the Heritage Asset, Candi Pari, how the assets are recognized, recorded and reported in the financial statements using a case study viewpoint.Design/Methodology/Approach: The Researchers collected the research data in three phases; first, the Researcher interviewed informants or sources from relevant department or manager of Candi Pari, namely the Balai Pelestarian Cagar Budaya, Jawa Timur (BPCB), second, the researcher checked documents of the Heritage Assets Candi Pari, how it’s recognized, as what, recorded, until now the value of Heritage Assets is, and the last data searching. Methods of data analysis in research is divided into three stages, first, data reduction, data selection, concentration, attention, abstraction and transforming the raw data from the field, second, the data display, presents data in the narrative and tables form to explain the phenomenon under study and the last is the conclusion.Research Findings: The results of this study is the recognition of the BPCB Jawa Timur is that Candi Pari is recorded as a plant asset, and Candi Pari is deliberate without value, so the Heritage Assets can not be traded. The amount of this recording conforms with based government accounting standards (PSAP) no. 07 the year 2010 statement no 69 that Heritage Assets must be recorded in the number of units without value.Theoretical contribution/Originality: The research contributes to find out how the accounting treatment of the Heritage Assets Candi PariPractitioner/Policy implication: Heritage assets are a material cultural heritage in the form of cultural heritage objects, cultural heritage buildings, cultural heritage structures, cultural heritage sites and cultural heritage areas on land or in water that needs to be preserved because they have essential values for history, science, education, religion, or culture through the determination process.Research limitation/Implication: The limitation of this research is that it has only a few informants since, in order to improve the effectiveness of research time, the researcher focuses more on the accounting treatment for Pari Temple as heritage assets.